A pre-formed Pyrogenic Factor Released by Lipopolysaccharide Stimulated Macrophages. Issue 5 (1994) - Zampronio Zampronio, A. R. A. R.; Melo Melo, M. C. C. M. C. C.; Silva Silva, C. A. A. C. A. A.; Pelá Pelá, I. R. I. R.; Hopkins Hopkins, S. J. S. J.; Souza Souza, G. E. P. G. E. P.
Abstract : The aim of this study was to investigate the pyrogenic activity of factor(s) released by rat peritoneal macrophages following a brief stimulation with LPS. The effect of this factor on the number of circulating leukocytes and serum Fe, Cu and Zn levels, was also evaluated. The possibility that the content of interleukin (IL)-1β, IL-6 and tumour necrosis factor (TNF) in the supernatant could explain the observations was investigated. Supernatant produced over a period of 1 h by peritoneal macrophages, following a 30 min incubation with LPS at 37°C, was ultrafiltered through a 10 000 MW cut-off Amicon membrane, sterilized, and concentrated 2.5, 5, 10 and 20 times. The intravenous (i.v.) injection of this supernatant induced a concentration-dependent fever in rats with a maximal response at 2 h. The pyrogenic activity was produced by macrophages elicited with thioglycollate and by resident cells. The supernatants also induced neutrophilia and reduction in Fe and Zn 6 h after the injection. Absence of activity in boiled supernatants, or supernatants from macrophages incubated at 4°C with LPS, indicates that LPS was not responsible for the activity. In vitro treatment with indomethacin (Indo), dexamethasone (Dex), or cycloheximide (Chx) did not modify the release of pyrogenic activity into the supernatant or its effects on the reduction in serum metal levels. Although Chx abolished the production of mediator(s) inducing neutrophilia, and Dex reduced the induction of IL-1β, TNF and IL-6, injection of the highest concentration of these cytokines detected in the supernatants did not induce fever. In vivo treatment with Dex, but not Indo, abolished the fever induced by the supernatant. These results suggest that macrophages contain pre-formed pyrogenic mediator(s), not related to IL-1β, IL-6 or TNF, that acts indirectly and independently of prostaglandtn. It also seems likely that the pyrogenic activity is related to the factor responsible for the reduction of serum Fe and Zn levels, but not the neutrophilia.